2008
DOI: 10.2319/012507-36.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Expression of SOX9 and Type II Collagen in Spheno-Occipital Synchondrosis of Mice after Mechanical Tension Stimuli

Abstract: Objective: To associate the expressions of SOX9 and type II collagen during growth in the synchondrosis with and without tensile stress in order to understand the role of these factors in the growth of cartilage in spheno-occipital synchondrosis. Materials and Methods: Sixty 1-day-old male BALB/c mice were randomly divided into experimental and control groups. Each group was subdivided again into five different time points which were 6, 24, 48, 72, and 168 hours. Each subgroup consisted of five mice. Each mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Cendekiawan et al 13 used tensile stress to stimulate expression of Sox9 and type II collagen, showing the same pattern of Sox9 and type II collagen expression from 6 hours to 168 hours. In the experimental groups, the expression of Sox9 and type II collagen reached a maximum level at 24 hours and 72 hours, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Cendekiawan et al 13 used tensile stress to stimulate expression of Sox9 and type II collagen, showing the same pattern of Sox9 and type II collagen expression from 6 hours to 168 hours. In the experimental groups, the expression of Sox9 and type II collagen reached a maximum level at 24 hours and 72 hours, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…This is in contrast to the 57% (P , .001) increase reported in the study by Cendekiawan et al In addition, we found an increased expression of 22.99% (P , .001) of type II collagen versus the 44.4% (P , .001) in their analysis. 13 This suggests 1 mM of quercetin is capable of producing a similar, but attenuated, amount of Sox9 and type II collagen expression compared with tensile stress. Although the overall effect of an increase of type II collagen expression is not big and the period of exposure of quercetin is short (several days), further research is needed to optimize the dosage of quercetin and to investigate the long-term effect of quercetin on growth.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mutations in genes encoding FGFRs have been identified as causes of Apert syndrome, Crouzon syndromes and Pfeiffer syndromes [5]. As for environmental effects, the use of an organ culture technique has revealed that synchondrosis is responsive to tensile mechanical stress and increased expression of various factors related to growth stimulation [115][116][117]. This series of studies was the first to show that growth across the synchondrosis can be modified mechanically.…”
Section: Recent Advancements In Cranial Base Researchmentioning
confidence: 99%
“…delivered tensile forces non‐invasively to the maxillae of rabbits and concluded that cyclic tension could stimulate the proliferation of chondrocytes and promote the expression of some extracellular matrix (ECM) . Organ culture studies found that mechanical stress applied to CBS elicited a series of molecular biological reactions including upregulated expression of Cbfa1, VEGF, PTHrP and Sox9 . Compared with an animal model and organ culture, direct mechanical protraction on cranial base synchondrosis chondrocytes (CBSCs) is more targeted and allows researchers to conduct further studies at the gene level .…”
Section: Introductionmentioning
confidence: 99%